Al-Takhlil al-Taqabuly fi Ta'lim al-Lughah al-'Arabiyyah - Muslim, Ahmad Bukhari (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2015)
Abstract This article explains systematically the nature of contrastive analysis in language learning. Throughout this article the writer investigates the development of contrastive analysis in the field of language learning, its main objectives, some hypotheses and criticisms on it as well. The writer goes on putting Indonesian and Arabic as an object of contrastive analysis as well as giving systematic steps for it.  Key Words:                   Contrastive analysis, Consonant, Vowel